Techno-economic performances of active condensation in a medium-scale biomass-fired district heating unit - Thibault Coppieters; Jérémie Fricker; Julien Blondeau (Case Studies in Thermal Engineering, 2022)
This work compares the economic viability of active and passive condensation in a medium-scale biomass combustion plant considering the variability of the return temperature and heat demand over the year. A typical District Heating plant with a total installed power of 9.5 MWth is considered. The economic feasibility is evaluated by means of the Net Present Value (NPV), Discounted Payback Period (DPP), and the Modified Internal Rate of Return (MIRR). Compared to passive condensation, the NPV of an active condensation plant is 66% higher and reduces the primary energy consumption by more than 50%. However, a higher initial investment and a higher DPP are calculated. Assuming constant return temperature and average heat demand over the year lead to an overestimation of the NPV by more than 110% for an active condensation plant and by more than 160% for a passive condensation plant. The NPV, DPP and MIRR are strongly impacted by a variation of the return temperature of the network.